JOMBLANG CAVE'S CONTEXTUAL DIVERSITY IN SUPPORTING ADVENTURE EXPERIENCE TOURISM AS A SUSTAINABLE CREATIVE ECONOMY - Diah Natarina; Agus Sachari (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2021)
The world tourism industry, which has been hit hard by the prolonged pandemic, has yet to show its revival. It has become a concern of the government, organizations communities and other private parties. The current situation did not allow people to have mobility. Some organizations considered that its time to evaluate and make recovery strategies to implement when the pandemic ends. It is Ollivaud and Haxton from the Organization for Economic Co-operation and Development providing advice on recovery steps. They say that the creative economy can help offer new products and services for new target groups away from conventional models of environmental or heritage-based cultural tourism: that can be through unconventional media advertisements, art creation in a specific building, and sound-and-light shows. Increasingly visitors are looking for experi-ence-based, instead of destination-based, tourism. Jomblang Cave located in Semanu Village, Gunung Kidul, since 2011 has wide-ly been well known as experience-based tourism, a form of the creative economy, which is currently experiencing a lack of visitors. This writing aims to optimize the contextual diversity of Jomblang Cave to upgrade itself to be ready to accept adventure tourists when the pandemic is gradually over. The research method used is the descriptive method with a qualitative approach. Data collection techniques by conducting interviews with managers, literature studies and site reviews. The data will be processed by the analytical method. The result is to prioritize the contextual diversity that owned, a form of the creative econo-my in the field of adventure tourism Jomblang Cave will remain sustainable.